Hybrid oxidation separation technology (HOST) for synergistic removal of recalcitrant pollutants in water - Lee, Wen Jie (Nanyang Technological University, 2022)
The omnipresence of emerging micropollutants (MPs) in the water body has become a worldwide concern in recent decades. Advanced oxidation process (AOP) has been recognised as a promising technology for effective MP abatement due to the generation of highly reactive oxidising species (e.g., HO•, Cl•, SO4•−, O2•−, 1O2, etc.). As compared to the homogeneous catalytic AOP, heterogeneous catalytic AOP is more advantageous due to its potential recovery and reusability of the solid catalyst. To date, many research studies employed metal oxides (MeOx) for heterogeneous catalytic ozonation and peroxymonosulfate (PMS) activation for MP degradation. However, most of the MeOx catalysts are applied in slurry reactors and thus require further separation and recovery which makes the process complicated and costly. Therefore, the integration of heterogeneous catalytic oxidation and ceramic membrane (CM) separation within the Hybrid Oxidation Separation Technology (HOST) system was developed in this study. In the HOST system, MeOx was immobilised onto/within the CM substrate to overcome the limitations of the slurry reactor. In the phase 1 of this study, the MeOx was successfully impregnated throughout the catalytic ceramic membranes (CCMs) via a citrate-assisted wet impregnation method. The conformal deposition of MeOx throughout the macroporous CM substrate could provide a microreactor environment for effective MP degradation and mineralisation within a short hydraulic retention time (HRT). The MeOx-impregnated CCMs (MeCCM, Me = Ce or Mn) were applied in the ozone (O3)-based HOST process operated under continuous dead-end filtration mode for degradation of a MP mixture containing bisphenol A (BPA), benzotriazole (BTA) and clofibric acid (CA). A higher degree of mineralisation up to 38% TOC removal was observed with the CeOx-impregnated CCM (CeCCM) over the MnOx-impregnated CCM (MnCCM) and pristine CM. Notably, the specific O3 consumption of the HOST process with CeCCM was recorded at 2.0 g O3(aq) g−1 TOC removal with a 13.7 s HRT. The trade-off between MP mineralisation and process throughput was revealed by investigating the effect of HRT on the hybrid process. The heterogenous catalytic ozonation mechanism of the hybrid process with CeCCM was proposed based on the identification of reactive oxygen species (ROS) and transformation products (TPs). In the phase 2 of study, a series of Ce/TiOx-functionalised CCMs (CeTi-CeCCMs) were fabricated via a two-step process. The first step involved citrate-assisted wet impregnation for conformal coating of CeOx throughout the CM substrate. The second step was to deposit a Ce-doped TiOx (CeTiOx) catalytic multilayer onto the CM outer surface via an acid-hydrolysed sol-gel dip-coating technique. Ce-dopant and block-copolymer Pluronic® P-123 was added to the acid-hydrolysed sol to fabricate a uniform Ce-doped TiOx layer with a hierarchically porous structure in which its porosity and pore size decrease from the innermost sublayer towards the final coated sublayer. The modifications adopted for the CeTi-CeCCM fabrication had only induced a marginal increase in the membrane resistance by 0.2×1011 m−1 as compared to the pristine CM which is favourable towards the membrane filtration process. The CeTi-CeCCM exhibited satisfactory antifouling property in the O3-based HOST process by retaining >92% of its initial permeability after 0.5-h operation with humic acid feed. Subsequently, the CeTi-CeCCM was employed for N,N-diethyl-3-methylbenzamide (DEET) degradation in the hybrid process and recorded a stable DEET degradation (up to 40%) and mineralisation with low specific O3(aq) consumption (1.4 g O3(aq) g−1 TOC removal) over multiple filtration-cleaning cycles operated with 10.8 s HRT. The degradation pathways of DEET were proposed and the ecotoxicity of its TPs was estimated using the Ecological Structure Activity Relationships (ECOSAR) program. In the final phase of this study, the application of Me/TiOx-functionalised CCM (MeTi-MeCCM) in the HOST process was extended for SO4•−-based AOP via PMS activation. Different MeTi-MeCCMs (Me = Ce or Co) were fabricated with different metal nitrate salts as precursors and employed for O3-based and PMS-based HOST processes. The robustness of the MeTi-MeCCMs was evaluated for simultaneous degradation of MPs (BPA, BTA, CA, DEET and sulfamethoxazole (SMX)). The CeTi-CeCCM/O3 HOST process could effectively degrade and mineralise the MPs with a low specific oxidant consumption of 0.7 M O3(aq) M−1 TOC removal, whereas the CoTi-CoCCM/PMS HOST process exhibited selective BPA and SMX degradation with 1.0 M PMS M−1 TOC removal. The robustness of the HOST processes was also tested with real water matrices obtained from the local water treatment and reclamation plants. The superior performance of the hybrid process was attributed to the novel MeTi-MeCCM architectural design, whereby the oxidant was utilised efficiently for the targeted MP degradation and mineralisation via the synergism of catalytic oxidation and membrane separation within the hybrid membrane reactor.